Market Entry of XPeng P7 to Japanese Electronic Car Market - Zhao, Tianyu; Halík, Jaroslav, 1961-; Siggillino, Federico; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
This bachelor thesis aims to analyze the Japanese eletric car market (PEST, SWOT and competition), and then decide whether XPeng P7, a Chinese EV business, should enter Japanese market, and how? By direct export or FDI? Therefore, This bachelor thesis paper defines three research questions: 1, what are the trends and development in Japanese electric car market? 2, what are the risks and opportunities in Japanese market for XPeng P7? 3, what are the most important influencing factors for XPeng P7 to enter Japanese EV market as exporter or foreign direct investor?
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses